Analisis Strategi Multiliterasi sebagai Pembelajaran PAI di Sekolah/Madrasah - Sri Wahyuni Harahap; Mardianto Mardianto; Muhammad Irwan Padli Nasution (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to analyze multiliteracy learning strategies in schools. The research method used is a literature study with a descriptive and analytical approach. The results of the study show that the use of multiliteracy learning strategies in schools has many benefits, such as improving reading, writing and speaking skills in different languages, as well as increasing the development of digital literacy. In addition, multiliteracy learning strategies can also improve critical and creative thinking skills, and facilitate the integration of different cultures. However, the implementation of this strategy has challenges that must be faced, such as a lack of understanding of the concept of multiliteracy by educators, availability of resources, and difficulties in determining what type of literacy should be taught. Therefore, it is recommended that schools pay attention to this multiliteracy learning strategy so that it can provide a holistic and effective learning experience for students.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//